The Role of MDR in the Recording of Digital Sales Transactions in Multi-Outlet Businesses: A Case Study of PT UBUU - Ashari, Aviva Putri; Widajantie, Tituk Diah (STIE Tri Bhakti, 2025)
This study aims to examine the role of the Merchant Discount Rate (MDR) in recording digital sales transactions within a multi-outlet company, using PT UBUU as a case study. The company has adopted QRIS-based digital payment systems and employs a centralized Point of Sale (POS) and ERP system to record transactions. However, MDR deductions are not automatically recorded in the POS system, requiring manual reconciliation by the head office team. This study uses a qualitative case study approach with data collected through in-depth interviews, observations, and documentation. Informants include the finance manager, supervisor, and administrative staff. The results show that the lack of integration between POS and ERP leads to data inconsistencies and reporting delays. MDR is also used strategically to determine efficient payment channels and to strengthen managerial control over cross-outlet accounting practices. From the perspective of the Theory of Planned Behavior (TPB), MDR recording is influenced by normative pressure from central management and staff perceptions of procedural convenience. These findings indicate that MDR serves a dual role—as a transaction cost and as a strategic tool for decision-making. This study concludes that MDR significantly affects the effectiveness of integrated, efficient, and accountable digital accounting systems in multi-outlet enterprises.